2018
DOI: 10.1029/2018tc004957
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Structure of Southwest China and Northern Vietnam From Ambient Noise Tomography: Implication for the Large‐Scale Material Transport Model in SE Tibet

Abstract: Several models have been proposed to describe the tectonic evolution of SE Tibet and its marginal areas. Hence, high-resolution crustal velocity models are essential to address this controversy. With waveform data from 73 broadband stations in southwest China and northern Vietnam, we invert for a 3-D shear wave velocity model of the crust and uppermost mantle from ambient noise tomography. Our model reveals that the midlower crustal low-velocity zone in the Xiaojiang Fault Zone extends farther southward across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 83 publications
(160 reference statements)
10
42
0
Order By: Relevance
“…8a). On a large scale, the presence of a LVZ in this sector is probably associated with a LVZ beneath central and southeastern Tibet (Ozacar and Zandt 2004;Xu et al 2007;Bai et al 2009;Li and van der Hilst 2010;Qiao et al 2018;Deng et al 2019). This evidence is also consistent with findings reported by Le et al (2008Le et al ( , 2009.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8a). On a large scale, the presence of a LVZ in this sector is probably associated with a LVZ beneath central and southeastern Tibet (Ozacar and Zandt 2004;Xu et al 2007;Bai et al 2009;Li and van der Hilst 2010;Qiao et al 2018;Deng et al 2019). This evidence is also consistent with findings reported by Le et al (2008Le et al ( , 2009.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Bai et al (2010) reported that they detected a LVZ in the northwestern part of the Indochina Peninsula. Recently, Qiao et al (2018) reported this LVZ extended to western side of the Dien Bien Phu fault based on results of ambient noise tomography. However, because of limited observations, the question of whether this LVZ extends to a broad area of northern Vietnam remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can explain the discrepancy between the CSS and our ANT model by anisotropic structure (transverse isotropy with slow vertical symmetry axis) in the LPC (see the text below). Weak VTI anisotropy explaining the velocity drop in the lower crust is in agreement with results of other authors elsewhere (e.g., Luo et al, 2013;Shapiro et al, 2004;and Qiao et al, 2018). The subtle v S decrease in the top of the LPC of the ANT model (see Figs.…”
Section: Bm Crust Images In Ant and Csssupporting
confidence: 92%
“…Additionally, the specific distribution, dynamic source and movement mechanism of the channel flow are not completely clear. In particular, the distribution of the channel flow given by different studies (Bai et al 2010;Bao et al 2015;Liu et al 2014;Qiao et al 2018) has significant differences. Thus, it is impractical to quantitatively study crustal vertical movement caused by the channel flow.…”
Section: Vertical Rates Caused By Deep Dynamic Activitiesmentioning
confidence: 99%